Indonesian English learners attitudes towards cheating, absenteeism, and gender: Interactions with L2 achievement - Subekti, Adaninggar Septi; Triyono, Sulis; Pranowo, Dwiyanto Djoko (Universitas Syiah Kuala, 2023)
The present study was conducted to find out Indonesian English as a Second/Foreign Language (L2) learners' attitudes towards cheating (AtC) in online English classes, as well as the possible influence of the combination of three variables, which are their AtC, absenteeism, and gender, on their L2 achievement as measured with their final grades. The study employed a survey method and was conducted by distributing an online questionnaire. In total, 164 Indonesian learners from various non-English departments at a university in Java participated in the study. Through descriptive statistics, it was found that generally learners reported their negative AtC in English class, suggesting disapproval towards cheating. Through multiple regression analysis, the study further found that the combination of learners AtC, absenteeism, and gender significantly influenced their L2 achievement, and the overall model could predict 34.5% of the total variance in L2 achievement. However, based on the beta coefficient of the three variables, only learners absenteeism and gender significantly affected their L2 achievement. As learners had higher absenteeism, they obtained lower L2 achievement. From a t-test analysis, female learners were found to have significantly better L2 achievement than their male counterparts. While the findings on the influence of absenteeism on L2 achievement generally conformed to literature in the field, the findings on the influence of AtC and gender on L2 achievement may suggest that further explorations may be necessary.